Math-Oriented Critical Thinking Skills of Elementary School Students Viewed from Cognitive Style - Huda, Syaiful; Khikmiyah, Fatimatul; Melindah, Vina (Jurnal Pendidikan MIPA, 2022)
The tendency to develop critical thinking skills has been carried out for a long time starting from the definition, indicators of mathematical critical thinking, and the practice of developing critical thinking. Critical thinking can be developed both individually and classically through learning. The purpose of this study was to analyze qualitatively the mathematical critical thinking process of SD Muhammadiyah Manyar students in terms of cognitive style. The research method is descriptive qualitative. The results of the analysis obtained students with FD cognitive style more than students with FI cognitive style. From the difference in numbers, it is in line with the analysis of the learning process where students need more teacher instruction in completing assignments. In addition, from the analysis of critical thinking aspects according to Facione (2013) of the 6 existing aspects there are 2 aspects that have not been achieved by students, namely explanation and self-regulation. Keywords: critical thinking skills, cognitive style, elementary school. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp373-384